Advances in cranberry insect pest management: A literature synthesis - Ben-Zvi, Yahel; Rodriguez-Saona, Cesar (Frontiers in Agronomy, 2023)
Over the past three decades, an increasing body of entomological research has been published on integrated pest management (IPM) in cranberries (Vaccinium macrocarpon Aiton). However, no paper has been published that synthesizes the existing literature. This paper fills this gap by analyzing 139 peer-reviewed and editor-reviewed articles that were data driven and had direct relevance to the subject of insect pests or insect pest management of V. macrocarpon. Results show that the top three studied insect pests of cranberries have been Sparganothis fruitworm (Sparganothis sulfureana Clemens), blackheaded fireworm (Rhopobota naevana Hübner), and cranberry fruitworm (Acrobasis vaccinii Riley). The regions with the most published entomological papers on cranberry IPM research have been New Jersey, Massachusetts, and Wisconsin in the United States, followed by British Columbia in Canada. Among IPM tactics, published research on chemical control, as well as on host-plant resistance, has increased likely due to recent advances on newer, reduced-risk insecticides and high-yielding cultivars; while published research focusing on behavioral control has declined likely due to the cost of these tactics. There are no consistent trends in published research on natural and biological control or cultural control. These historical research trends are important when considering regulatory changes on insecticide use, such as the Food Quality Protection Act of 1996 in the United States, which resulted in banning and restrictions of certain broad-spectrum insecticides. As more insecticides are banned or restricted and global and organic cranberry production increases, we anticipate further advances in research related to sustainable IPM tactics.